2016
DOI: 10.3389/fncel.2016.00265
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Mice Are Resilient to Alcohol Withdrawal-Induced Anxiety and Changes in Indices of Glutamate Function within the Nucleus Accumbens

Abstract: Binge-drinking is the most prevalent form of alcohol abuse and while an early life history of binge-drinking is a significant risk factor for subsequent alcoholism and co-morbid affective disorders, relatively little is known regarding the biobehavioral impact of binge-drinking during the sensitive neurodevelopmental period of adolescence. In adult mice, a month-long history of binge-drinking elicits a hyper-glutamatergic state within the nucleus accumbens (Acb), coinciding with hyper-anxiety. Herein, we emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
124
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(171 citation statements)
references
References 112 publications
24
124
5
Order By: Relevance
“…Similarly, chronic alcohol produces a 25% increase in kinase activity in rat cortical astrocytes (Smith and Navratilova, 1999). Results from in vivo studies show that forced exposure to alcohol in the drinking water from conception through postnatal day 8, 30, or 90 upregulates CaMKIIα protein in rat cortex (Mahadev et al, 2001) and that binge-like drinking (~6 g/kg/day) increases expression of CaMKII in the nucleus accumbens of adult mice (Lee et al, 2016). We have shown that voluntary alcohol drinking (24-h home-cage) increases total CaMKIIα protein expression in mouse amygdala and nucleus accumbens, and that low-dose operant self-administration (~1 g/kg/day) increases pCaMKII-T286 IR in the amygdala immediately after intake (Salling et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, chronic alcohol produces a 25% increase in kinase activity in rat cortical astrocytes (Smith and Navratilova, 1999). Results from in vivo studies show that forced exposure to alcohol in the drinking water from conception through postnatal day 8, 30, or 90 upregulates CaMKIIα protein in rat cortex (Mahadev et al, 2001) and that binge-like drinking (~6 g/kg/day) increases expression of CaMKII in the nucleus accumbens of adult mice (Lee et al, 2016). We have shown that voluntary alcohol drinking (24-h home-cage) increases total CaMKIIα protein expression in mouse amygdala and nucleus accumbens, and that low-dose operant self-administration (~1 g/kg/day) increases pCaMKII-T286 IR in the amygdala immediately after intake (Salling et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of alcohol exposure induced by binge-like alcohol drinking also increase CaMKII protein expression in the nucleus accumbens (Lee et al, 2016). At the mechanistic level, pharmacological inhibition of CaMKII activity in the amygdala reduces operant alcohol self-administration in C57BL/6J mice (Salling et al, 2016) and alcohol-preferring P-rats (Cannady et al, 2016), indicating that the reinforcing effects of alcohol require CaMKII activation in the amygdala.…”
Section: Introductionmentioning
confidence: 99%
“…For example, we demonstrated recently that, in contrast to adult binge-drinking mice that exhibit robust anxiety-like behavior during early (24 h) withdrawal across several conventional behavioral tests of negative affect (e.g., light-dark shuttle box, novel object encounter, Porsolt swim test, elevated plus-maze), adolescent binge-drinking mice resemble water-drinking controls (Lee et al, 2015, 2016). In the present study, we sought to expand these findings to assess the adult consequences of adolescent binge-drinking on negative affect and subsequent alcohol-drinking.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work in our laboratory has successfully recapitulated these age-related differences in withdrawal-induced negative affect using a mouse model of voluntary binge-drinking. We have shown that adult alcohol-drinking mice exhibit increased behavioral indices of anxiety during early (24 h) withdrawal (Lee et al, 2016). This elevated anxiety coincides with increased expression of metabotropic glutamate receptor 5 (mGlu5) within the nucleus accumbens shell (AcbSh) during acute withdrawal, as indicated by western blotting (Cozzoli et al, 2012; Obara et al, 2009; Lee et al, 2016, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that adult alcohol-drinking mice exhibit increased behavioral indices of anxiety during early (24 h) withdrawal (Lee et al, 2016). This elevated anxiety coincides with increased expression of metabotropic glutamate receptor 5 (mGlu5) within the nucleus accumbens shell (AcbSh) during acute withdrawal, as indicated by western blotting (Cozzoli et al, 2012; Obara et al, 2009; Lee et al, 2016, 2017b). In contrast, adolescent drinkers were resilient to both withdrawal-induced hyperanxiety and increased mGlu5 expression within the AcbSh during early withdrawal (Lee et al, 2016, 2017b).…”
Section: Introductionmentioning
confidence: 99%